Quality of life Evaluation in patients receiving Steroids (the QuESt tool): initial development in children and young people with acute lymphoblastic leukaemia. Issue 3 (23rd December 2015) - Adams, M; Robling, M; Grainger, J; Tomlins, J; Johnson, A; Morris, S; Velangi, M; Jenney, M
Abstract : Background: The powerful cytotoxic and immunomodulatory effects of corticosteroids are an important element of the success that has been achieved in the treatment of acute lymphoblastic leukaemia (ALL). In addition to physical side effects, corticosteroids can adversely influence behaviour, cognitive function and mood leading to significantly impaired quality of life (QoL). A number of tools exist for assessing QoL, but none of these specifically examines changes attributable to steroids. Methods: Children and young adults aged 8–24 years and parents of children receiving maintenance therapy for ALL from four UK centres were invited to participate. The study comprised three stages carried out over 2 years: (1) focus groups and interviews where participants were asked to describe their experiences of dexamethasone; (2) analysis of questionnaires sent to healthcare professionals and patients to evaluate the importance and relevance of the questions; and (3) cognitive interviewing. Results: Interpretative phenomenological analysis of focus group and interview transcripts identified that dexamethasone adversely influenced behaviour, appetite, body image, mood and family relationships. 157 electronic survey responses were analysed leading to further item development. Cognitive interviewing confirmed face validity and internal consistency. QuESt comprises 28 questions within four domains and has three age-specific versions. Conclusions: QuESt is the first treatment-specific QoL measure for children and young adults receiving corticosteroids. It can be completed in 10–15 min by children aged ≥8 years. Further validity and reliability testing will be undertaken. Although the initial application is for ALL, QuESt may also be a valuable tool for understanding the impact of corticosteroids in other paediatric conditions.